Targeting USP9X–AMPK Axis in ARID1A-Deficient Hepatocellular CarcinomaSummary - Feng-Kun Zhang; Qian-Zhi Ni; Kang Wang; Hui-Jun Cao; Dong-Xian Guan; Er-Bin Zhang; Ning Ma; Yi-Kang Wang; Qian-Wen Zheng; Sheng Xu; Bing Zhu; Tian-Wei Chen; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Background & Aims: Hepatocellular carcinoma (HCC) is a highly heterogeneous solid tumor with high morbidity and mortality. AT-rich interaction domain 1A (ARID1A) accounts for up to 10% of mutations in liver cancer, however, its role in HCC remains controversial, and no targeted therapy has been established. Methods: The expression of ARID1A in clinical samples was examined by Western blot and immunohistochemical staining. ARID1A was knocked out by Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) in HCC cell lines, and the effects of glucose deprivation on cell viability, proliferation, and apoptosis were measured. Mass spectrometry analysis was used to find ARID1A-interacting proteins, and the result was verified by co-immunoprecipitation and Glutathione S Transferase (GST) pull-down. The regulation of ARID1A target gene USP9X was investigated by chromatin immunoprecipitation, Glutathione S Transferase (GST) pull-down, luciferase reporter assay, and so forth. Finally, drug treatments were performed to explore the therapeutic potential of the agents targeting ARID1A-deficient HCC in vitro and in vivo. Results: Our study has shown that ARID1A loss protected cells from glucose deprivation–induced cell death. A mechanism study disclosed that AIRD1A recruited histone deacetylase 1 via its C-terminal region DUF3518 to the promoter of USP9X, resulting in down-regulation of USP9X and its target protein kinase AMP-activated catalytic subunit α2 (PRKAA2). ARID1A knockout and a 1989∗ truncation mutant in HCC abolished this effect, increased the levels of H3K9 and H3K27 acetylation at the USP9X promoter, and up-regulated the expression of USP9X and protein kinase AMP-activated catalytic subunit α2 (PRKAA2), which mediated the adaptation of tumor cells to glucose starvation. Compound C dramatically inhibited the growth of ARID1A-deficient tumors and prolongs the survival of tumor-bearing mice. Conclusions: HCC patients with ARID1A mutation may benefit from synthetic lethal therapy targeting the ubiquitin-specific peptidase 9 X-linked (USP9X)–adenosine 5‘-monophosphate–activated protein kinase (AMPK) axis.